2017
DOI: 10.1371/journal.pone.0181491
|View full text |Cite
|
Sign up to set email alerts
|

Assessing intragenomic variation of the internal transcribed spacer two: Adapting the Illumina metagenomics protocol

Abstract: Primary and secondary structural data from the internal transcribed spacer two (ITS2) have been used extensively for diversity studies of many different eukaryotic organisms, including the green algae. Ease of amplification is due, at least in part, to the fact that ITS2 is part of the tandemly-repeated rRNA array. The potential confounding influence of intragenomic variability has yet to be addressed except in a few organisms. Moreover, few of the assessments of intragenomic variation have taken advantage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In addition, Alanagreh et al . (2017) reported that the dominant haplotype was usually evident from the Sanger sequencing, similar as in cloning approach.…”
Section: Methodsmentioning
confidence: 92%
“…In addition, Alanagreh et al . (2017) reported that the dominant haplotype was usually evident from the Sanger sequencing, similar as in cloning approach.…”
Section: Methodsmentioning
confidence: 92%
“…In past years, there has not been consistent agreement about the selection of ITS1 or ITS2 in studies of fungal diversity. Nilsson et al [ 27 ], Ihrmark et al [ 28 ] and Alanagre et al [ 29 ] stated that ITS2 was the better choice for 454 pyrosequencing or sequencing with Illumina platforms. However, Wang et al [ 22 ] showed that ITS1 might be a better taxonomic DNA barcode than ITS2 in eukaryotes, based on in silico analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 18S rDNA marker is not sufficiently variable to distinguish among closely related taxa (Hall et al 2010). In contrast, the internal nuclear rDNA transcribed spacer 2 (ITS2 rDNA) inherits high taxonomic resolution, but also in some cases high intragenomic variation (Thornhill et al 2007;Simon & Weiss 2008;Alanagreh et al 2017), which may affect OTU (Operational Taxonomic Unit) clustering and taxonomic identification. Since the rRNA cassette can vary in copy numbers per organism and the ITS regions are free to independently drift within the same organism, a potential overestimation of OTUs may occur, especially in some fungal species (i.e., one species can split into several OTUs (Lindner & Banik 2011;Lindner et al 2013).…”
Section: Methodsmentioning
confidence: 99%